Broad‐spectrum cytotoxicity to cancer cells of Brevilaterin C from Brevibacillus laterosporus and its specific mechanism on human epidermal cancer cells. Issue 7 (3rd June 2022) - Chen, Zhou; Wang, Lulu; Hong, Dan; Liu, Yangliu; Han, Panpan; Li, Siting; Jia, Yingmin
Abstract: Antimicrobial peptides (AMP) from Brevibacillus laterosporus have good prospects as clinical treatments for cancer. Nevertheless, details about their anticancer spectrum and mode of cytotoxicity remain poorly understood. A newly found AMP (named Brevilaterin C) secreted by B. laterosporus S62‐9 exhibited strong inhibition on almost cancer cell lines examined at a concentration of 8 µg/ml but was relatively safe for normal cells. We further systematically examined its cytotoxicity and mechanism toward human epidermal cancer cell A431. A dosage of 3 µg/ml of Brevilaterin C could significantly increase lactate dehydrogenase release of tumor cells. Moreover, it could remarkably increase the ratio of apoptosis and reactive oxygen species generation of A431, indicating effective induction of apoptosis. Moreover, the formation of JC‐1 aggregates was effectively prevented by a low concentration of Brevilaterin C, indicating its effective induction of A431's apoptosis. Brevilaterin C exhibited broad‐spectrum cytotoxicity to cancer cells, indicating a good potential prospect in the medical field.